Application of a degenerate diffusion method in 3D medical image processing - Máca, Radek; Beneš, Michal (Proceedings of the Conference Algoritmy, 2015)
In this contribution, we present the application of the level set formulation of the geodesic active contours model and its 3D semi-implicit complementary volume discretization to the segmentation of 2D+t cardiac MRI (CMR) data. The appropriate adujstment of algorithm parameters is explained. In particular, the algorithm is applied to the segmentation of the left and right heart ventricle from the time series of 2D+t cine CMR data.